HIV Cure Research: Risks Patients Expressed Willingness to Accept. Issue 6 (19th November 2019) - Kratka, Allison; Ubel, Peter A.; Scherr, Karen; Murray, Benjamin; Eyal, Nir; Kirby, Christine; Katz, Madelaine N.; Holtzman, Lisa; Pollak, Kathryn; Freedburg, Kenneth; Blumenthal‐Barby, Jennifer
ABSTRACT: Despite doing well on antiretroviral therapy, many people living with HIV have expressed a willingness to accept substantial risks for an HIV cure. To date, few studies have assessed the specific quantitative maximal risk that future participants might take; probed whether, according to future participants, the risk can be offset by the benefits; and examined whether taking substantial risk is a reasonable decision. In this qualitative study, we interviewed 22 people living with HIV and used standard gamble methodology to assess the maximum chance of death a person would risk for an HIV cure. We probed participants' reasoning behind their risk‐taking responses. Conventional inductive content analysis was used to categorize key themes regarding decision‐making. We found that some people would be willing to risk even death for an HIV cure, and some of their reasons were plausible and went far beyond the health‐related utility of an HIV cure. We contend that people's expressed willingness to take substantial risk for an HIV cure should not be dismissed out of hand.